Effects of a specially designed fermented milk product containing probiotic Lactobacillus casei DN-114 001 and the eradication of H. pylori in children: a prospective randomized double-blind study - Sýkora, Josef; Valecková, Kristýna; Amlerová, Jana; Siala, Konrad; Dedek, Petr; Watkins, Stephen; Varvarovská, Jana; Stozický, Frantisek; Pazdiora, Petr; Schwarz, Jan (Journal of clinical gastroenterology, 2005)
GOALS: To determine the efficacy of triple therapy supplemented with a specially designed fermented milk product containing specific probiotic Lactobacillus casei (L. casei) DN-114 001 strain on Helicobacter pylori eradication in children. BACKGROUND: Lactobacillus species possess in vitro activity against H. pylori. There are no consistent data on the impact of eradication therapy supplemented with probiotics on H. pylori cure rates in childhood in vivo. STUDY: Multicenter, prospective, randomized, double-blind controlled study. Eighty-six symptomatic H. pylori-positive children were randomized either to receive the control treatment of omeprazole, amoxicillin, and clarithromycin (OAC) for 7 days or the test treatment of omeprazole, amoxicillin, and clarithromycin for 7 days supplemented with fermented milk (Actimel) containing L. casei DN-114 001 (OAC-LC), for 14 days. H. pylori status was assessed at 4 weeks following therapy using two noninvasive tests. RESULTS: Intention-to-treat (ITT) based eradication rates for the OAC-LC group were 84.6% (95% CI, 71.2%-95.5%), and 91.6% (95% CI, 76.9%-98.2%) by per-protocol (PP) analysis. Eradication in the OAC group was 57.5% (95% CI, 42.2%-72.3%) in the ITT set and 61.3% (95% CI, 44.4%-75.0%) in the PP group. Eradication success was higher in the OAC-LC group compared with the OAC group in both ITT (P=0.0045) and PP analysis (P=0.0019). Primary resistance for clarithromycin could be determined in 21.2%. Side effects were infrequent. Drug compliance was good throughout the study. CONCLUSION: Supplementation with fermented milk, containing live special probiotic L. casei DN-114 001, confers an enhanced therapeutic benefit on H. pylori eradication in children with gastritis on triple therapy.
Keywords: kysané mléčné výrobky; Lacticaseibacillus casei; Antigens, Bacterial; gastroskopie; Humans; žaludeční sliznice; Gastritis; dítě; Double-Blind Method; Child; Female; antigeny bakteriální; výsledek terapie; dvojitá slepá metoda; lidé; gastritida; Lactobacillus casei; ženské pohlaví; Follow-Up Studies; Helicobacter Infections; Helicobacter pylori; Male; Gastric Mucosa; Treatment Outcome; Cultured Milk Products; probiotika; mužské pohlaví; prospektivní studie; Gastroscopy; Probiotics; infekce vyvolané Helicobacter pylori; následné studie; Prospective Studies